INTER-INDUSTRY BALANCE (INPUT-OUTPUT) MODELS AS A TOOL FOR ANALYZING SECTORAL INTERDEPENDENCE, RESOURCE ALLOCATION EFFICIENCY, AND STRUCTURAL IMBALANCES IN THE NATIONAL ECONOMY - O‘rozov Azamat Otaboyevich; Salayeva Guli Mansurbek qizi (Antis Publisher, 2026)
Objective: Inter-industry balance models serve as an important scientific and methodological tool for analyzing the interrelationships between different sectors of the economy and the allocation of resources. Method: The foundation of these models is the input-output model developed by Vasiliy Leontief. This approach makes it possible to determine the balance between the resources each sector receives from other sectors and the products it supplies to them. Results: Inter-industry balance models can be used to forecast economic growth rates, formulate investment policies, improve production efficiency, and develop regional development strategies. Novelty: In addition, these models play a significant role in optimizing the structure of the national economy, ensuring efficient resource utilization, and maintaining economic equilibrium.